Difference between revisions of "1983 AHSME Problems/Problem 18"
Line 9: | Line 9: | ||
Let <math>y = x^2 + 1</math>. Then <math>x^2 = y - 1</math>, so we can write the given equation as | Let <math>y = x^2 + 1</math>. Then <math>x^2 = y - 1</math>, so we can write the given equation as | ||
− | <math> | + | <math>f(y) &= x^4 + 5x^2 + 3 \\ |
− | f(y) &= x^4 + 5x^2 + 3 \\ | ||
&= (x^2)^2 + 5x^2 + 3 \\ | &= (x^2)^2 + 5x^2 + 3 \\ | ||
&= (y - 1)^2 + 5(y - 1) + 3 \\ | &= (y - 1)^2 + 5(y - 1) + 3 \\ | ||
&= y^2 - 2y + 1 + 5y - 5 + 3 \\ | &= y^2 - 2y + 1 + 5y - 5 + 3 \\ | ||
− | &= y^2 + 3y - 1. | + | &= y^2 + 3y - 1.</math> |
− | |||
Then substituting <math>x^2 - 1</math>, we get | Then substituting <math>x^2 - 1</math>, we get | ||
− | <math> | + | <math>f(x^2 - 1) &= (x^2 - 1)^2 + 3(x^2 - 1) - 1 \\ |
− | f(x^2 - 1) &= (x^2 - 1)^2 + 3(x^2 - 1) - 1 \\ | ||
&= x^4 - 2x^2 + 1 + 3x^2 - 3 - 1 \\ | &= x^4 - 2x^2 + 1 + 3x^2 - 3 - 1 \\ | ||
− | &= \boxed{x^4 + x^2 - 3}. | + | &= \boxed{x^4 + x^2 - 3}.</math> |
− | |||
The answer is (B). | The answer is (B). |
Revision as of 13:56, 1 July 2017
Problem:
Let be a polynomial function such that, for all real
,
For all real
,
is
(A) (B)
(C)
(D)
(E) none of these
Solution:
Let . Then
, so we can write the given equation as
$f(y) &= x^4 + 5x^2 + 3 \\
&= (x^2)^2 + 5x^2 + 3 \\
&= (y - 1)^2 + 5(y - 1) + 3 \\
&= y^2 - 2y + 1 + 5y - 5 + 3 \\
&= y^2 + 3y - 1.$ (Error compiling LaTeX. Unknown error_msg)
Then substituting
, we get
$f(x^2 - 1) &= (x^2 - 1)^2 + 3(x^2 - 1) - 1 \\
&= x^4 - 2x^2 + 1 + 3x^2 - 3 - 1 \\
&= \boxed{x^4 + x^2 - 3}.$ (Error compiling LaTeX. Unknown error_msg)
The answer is (B).